Enhancing competitive advantage through successful lean realisation within the Aviation Maintenance Repair and Overhaul (MRO) industry - Ayeni, P. (Cranfield University, 2015)
Purpose: Lean is increasingly being applied within the aviation Maintenance and Repair (MRO) Industry to mitigate industry challenges. This Lean application is premised on its success within other industrial contexts particularly the automotive industry. Furthermore, many organisations within automotive industry have attributed their enhanced competitive positioning to the Lean application. Indeed, Toyota (a pioneer of Lean) present Lean as a key proponent to its global success. However, with literature suggesting that there cannot be a direct transference of Lean from one industry to another and with the MRO having distinct characteristics different from the automotive industry, this research seeks to present how competitive advantage can be achieved through successful Lean realisation. Design/Methodology/Approach: The status of MRO Lean engagements presented is first presented based on the syntheses of literature review and empirical study (facilitate by an industry-wide survey). The means through which the MRO realises its value proposition is established and the structural assessment of the MRO industry as it pertains to competitiveness is also defined. The role of Lean in enhancing the value delivery system to enhance competitive positioning is operationalised through a case study. Findings: Using Porter’s forces of competition, this research establishes the competitive MRO landscape revealing the distinct characteristics of the MRO industry and how Lean can be accurately appropriated to enhance competitive advantage. The MRO Value Delivery System (VDS) is also delineated providing the complete system within which Lean is to be deployed (as opposed to the prevalent limited application of Lean in operational context alone). The case exemplar successfully validates and operationalises the approach to Lean application within MRO to enhance competitive advantage. Research Limitations: A case study example was used for this research, and whilst the outcomes were consistent with the research proposal, it still requires wider validation. Practical and Social Implications: This research demystifies and helps MRO organisations in assessing their Lean engagements but also in provide a roadmap and informs their strategy in improving their competitive status through Lean realisation.